2021
DOI: 10.31014/aior.1993.04.02.211
|View full text |Cite
|
Sign up to set email alerts
|

Higher Education in Pakistan: Challenges, Opportunities, Suggestions

Abstract: Higher education provides opportunities to censoriously reveal the cultural, moral, socio-economic, and spiritual issues faced by the human race. Pakistan's higher education system has many institutional drawbacks includes a lack of quality management, institutional structure, and knowledge gaps between cross-culture educations systems to improve the efficiency of the current higher education system in Pakistan. To make Pakistan an educational center, Pakistan must strengthen the education system by developing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 10 publications
0
25
0
Order By: Relevance
“…Critical perspectives, and strict contention displayed by the overall population towards biotechnology and genetically changed organic entity causing deterrent in the advancement of this field [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Critical perspectives, and strict contention displayed by the overall population towards biotechnology and genetically changed organic entity causing deterrent in the advancement of this field [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…It was found that Pakistan is a developing country and faces many challenges, including a lack of resources, a rapidly growing population, and an education system in need of reform (Larik, 2021). These challenges have a significant impact on teachers' retention, as teachers are often the first to leave an institution due to a lack of job satisfaction or because they find other opportunities (Murtaza & Hui, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Pakistan's rapidly growing population places even more strain on the education system. A lack of resources and an education system that needs reform will continue to be major factors in teacher retention in Pakistan (Murtaza & Hui, 2021;Moin & Hassan, 2021)…”
Section: Literature Reviewmentioning
confidence: 99%
“…First, teaching performance (TP) is comprised of outputs related to teaching and learning goals for higher education systems (Agasisti & Bertoletti, 2019). TP is one of the problem areas in the Pakistani HE context due to several reasons including inappropriate/old content, lack of latest knowledge, poor teaching methods, poor learning skills, poor evaluation systems, the superficial teacher recruitment process with political interference (Banuri, 2021;Murtaza & Hui, 2021); disciplinary problems among students, academic scams by teachers, shorter working days (Hoodbhoy, 2009); and lack of faculty members with PhDs (Hoodbhoy, 2009;Murtaza & Hui, 2021).…”
Section: Higher Education Performancementioning
confidence: 99%